Impact of the surgeon's experience on the postoperative outcome: a retrospective analysis of non-melanoma skin cancers of the head and neck region - Felcht, Moritz; Faulhaber, Jörg; Linder, Anna Sophie Maria; Goerdt, Sergij; Koenen, Wolfgang (Journal der Deutschen Dermatologischen Gesellschaft, 2010)
Background: Treatment of choice for non-melanoma skin cancers is surgical excision. No study has analyzed the impact of the dermatologic surgeon's experience on the postoperative outcome. Patients and Methods: In a single center, retrospective study, 196 cases of non-melanoma skin cancer of the head and neck treated with micrographically-controlled surgery were categorized with regard to type of tumor, location, size of defect, number of stages, complications, recurrence rate and cosmetic result. These data were analyzed in respect of the surgeon's experience (dermatology attendings [AT], senior residents with experience in dermatosurgery [SR], junior residents with less experience in dermatosurgery [JR]). Results: AT and SR excised tumors in toto at roughly the same rate (AT: 42/75; SR: 59/104), JR less frequently (3/6). The patients graded 97 % of the scars as very good to satisfactory. The grading of smaller defects (< 4 cm2) was not influenced by the surgeon's experience. Larger defects were graded equally in the two groups AT and SR. The complication rate was similar in all three groups, even though larger defects were treated by the attendings (AT). Conclusions: Micrographically-controlled surgery followed by plastic reconstruction is the treatment of choice for non-melanoma skin tumors of the head and neck area. Cosmetic results are excellent. Minor procedures can be performed by residents during their training; larger defects require more experience in dermatosurgery.